Imaging zebrafish neural circuitry from whole brain to synapse - Leung, Louis C.; Wang, Gordon X.; Mourrain, Philippe (Frontiers in Neural Circuits, 2013)
Recent advances in imaging tools are inspiring zebrafish researchers to tackle ever more ambitious questions in the neurosciences. Behaviorally fundamental conserved neural networks can now be potentially studied using zebrafish from a brain wide scale to molecular resolution. In this perspective, we offer a roadmap by which a zebrafish researcher can navigate the course from collecting neural activities across the brain associated with a behavior, to unraveling molecular identities and testing the functional relevance of active neurons, in order to reach important conclusions on how neural networks result in behaviors and changes in synaptic connectivity.